The crisis of humanism (II): the end of the Jewish center in Germany - Shveid, Eliʿezer (A history of modern Jewish religious philosophy, 2022)
The last generation of German Jewish philosophers -- the best known (Buber, Rosenzweig, Baeck, Strauss, Scholem) and the less known (Breuer, Birnbaum, Klatzkin, Guttmann) -- are thoroughly explicated here with generous primary text citations appearing in English for the first time.